UPAYA MENINGKATKAN HASIL BELAJAR SISWATENTANG PESAN MELALUI TELEPON DENGAN METODE PEMODELAN SISWA KELAS IV SD NEGERI 111 PEKANBARU - Artuti ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Low student learning outcomes due to less precise selection method of learning that suits the subject matter presented to the students. Efforts to overcome this need for a method or a proper way so that every student is able to receive information in every lesson well. Stages for easy entry of information, namely, listening, writing or drawing and then view and conduct their own experiments. To the researchers conduct classroom action research by applying methods of modeling. The subjects were fourth grade students of SD Negeri 111 Pekanbaru with the number of 30 students. This research was conducted by 2 cycles. Data collection techniques used were observation activities of teachers and students and the achievement test. Research suggests that the application of modeling methods to improve learning outcomes language on the material Indonesia message over the phone, this is evidenced by: (a) increase the activity of the teacher, in the first cycle of the first meeting, please obtain a category with a score of 35 (58.33%). At a meeting of the second cycle I earn good category with a score of 43 (71.67%). Cycle II meeting I obtained good category with a score of 49 (81.67%). At the second meeting of the second cycle of activity students gain Very Good category with a score of 53 (88.33%). Besides the activities of students in the first cycle of meetings I obtain a score of 34 (56.67%) with a category, please. At a meeting of the second cycle I obtained a score of 46 (76.67%) with good category. Cycle II meeting I obtained a score of 51 (85.00%) to the category of Very Good. At the second meeting of the second cycle of activity students obtain a score of 57 (95.00%) category of Very Good; and (b) learning outcomes has increased, on the basis of scores obtained an average value of 48.38 with a low category. UH in the first cycle obtain an average value of 72.00 with the high category. In the second cycle UH earned an average value of 76.50 with the high category. mastery learning of individual students in each cycle has increased. On the basis of completeness scores of individual students obtained a score of 36.67% (11 students). At UH cycle I obtained a score of 60.00% (18 students). UH second cycle increased with the acquisition of a score of 86.67% (26 students).